2011
DOI: 10.1037/a0023016
|View full text |Cite
|
Sign up to set email alerts
|

The unique contributions of positive and negative religious coping to posttraumatic growth and PTSD.

Abstract: The current study assessed relationships between religious coping, gender, posttraumatic stress disorder (PTSD) and posttraumatic growth (PTG). A sample of 1,016 participants completed measures of these constructs during an online mass testing procedure. Overall, positive religious coping was more strongly related to PTG and negative religious coping was more strongly related to PTSD. These relationships remained significant after controlling for traditional coping methods, gender, and race. In addition, posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
111
3
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 46 publications
14
111
3
4
Order By: Relevance
“…These results comply with other findings related to strict correlations between coping through REL and PTG. 16 McMillen and Cook 17 showed that coping through turning to REL shows a significant relationship with positive outcomes of SCI.…”
Section: Discussionmentioning
confidence: 99%
“…These results comply with other findings related to strict correlations between coping through REL and PTG. 16 McMillen and Cook 17 showed that coping through turning to REL shows a significant relationship with positive outcomes of SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Facing challenging situations, individuals draw on religious coping methods as a part of their general orienting and meaning systems, which in turn influence their abilities to cope with adversity and life stress [24,31]. It is especially discernable in coping with major stress situations e.g., among patients diagnosed with cancer [39] or people who experienced traumatic events [40]. The orienting and meaning systems appear to influence the types of coping strategies that are used in specific situations.…”
Section: The Role Of Religious Coping In Increasing Well-beingmentioning
confidence: 99%
“…For example, a positive between the experience of childhood abuse and PTS [31], it dampened the relationship between direct traumatic events and PTG [32], and it strengthened the relationship between stress and depression [33]. Positive RC also acts as a mediator or an explanatory process, but in an opposite way, because it partially mediated the relationship between gender and PTG [16], or it totally mediated the relationship between subject severity and PTG [8].…”
Section: Introductionmentioning
confidence: 99%